Development of interactive learning media based on Google Sites on energy source materials for grade III elementary schools - Asika (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
This study aims to determine the validity of Google Sites-based interactive learning media in Chapter 4 Getting to Know Energy Topic B Energy Sources Around Us for grade III elementary school students. This type of research is research and development or Research and Development (R&D). The development design used in this study is a 4D model consisting of four stages, namely define, design, develop, and disseminate, but in this study the researcher limited it to the develop stage. The subjects in this study are material and design experts. The instrument used is an expert product validation questionnaire. This study carried out an expert validity test. The assessment of the design aspect got an average percentage of 80%, the material and content aspects got an average of 70%, and the navigation and accessibility aspects got an average of 80%, Based on the results of the study, there is a conclusion that the teaching materials based on Google Sites in Chapter 4 Getting to Know Energy Topic B Energy Sources Around Us in grade III elementary school are in the valid category, but need to be revised.